Is a Vessel-Sealing System Useful for Resection of Anterior Mediastinal Mass? - Santini, Mario; Fiorelli, Alfonso; Vicidomini, Giovanni; Messina, Gaetana; Accardo, Marina (The Thoracic and Cardiovascular Surgeon, 2015)
Objective To valuate if the LigaSure (Valleylab, Boulder, Colorado, United States) vessel-sealing system could reduce operative time, intraoperative blood loss, drainage duration, and hospital stay in patients with anterior mediastinal mass undergoing open resection.Methods Forty consecutive patients having resection of anterior mediastinal mass were randomized into two groups according to whether LigaSure was used (n = 20) or not (n = 20). Tumor size, operative time, intraoperative blood loss, chest tube output and duration, length of hospital stay, morbidity, and mortality were prospectively recorded, then intergroup differences were statistically analyzed.Results Both groups were well matched for age, tumor size, pathologic diagnosis, and incidence of complications. LigaSure significantly reduced operative duration (p < 0.0001) compared with the traditional technique but without leading to any significant reduction in intraoperative blood loss (p = 0.2), chest tube output (p = 0.2) and duration (p = 0.2), and length of hospital stay (p = 0.5).Conclusions The reduced operative time using LigaSure translates into less exposure to general anesthesia, which is particularly important for patients with myasthenia and potentially reducing cost.
Keywords: LigaSure; mediastinal resection; mass